Experimental study to separate surface and bulk contributions of light-induced degradation in crystalline silicon solar cells. Issue 2 (20th August 2015) - Basnyat, Prakash; Sopori, Bhushan; Devayajanam, Srinivas; Shet, Sudhakar; Binns, Jeff; Appel, Jesse; Ravindra, Nuggehalli M.
Abstract : In this paper, investigations toward understanding the bulk and surface components of light-induced degradation (LID) in low-iron crystalline silicon (Si) solar cells are explored. The bulk effects, arising from boron–oxygen defects, are determined by comparing degradation of cell parameters and their thermal recovery, with that of the minority-carrier lifetime (τ) in sister wafers. It is found that the lifetime of wafer, τ, is recovered fully after annealing, but cell efficiency is recovered partially. It is also shown that cells having SiN:H coating experience a surface degradation (ascribed to surface recombination). The surface LID is seen as an increase in the q /2 kT component of the dark saturation current ( J 02 ). The surface LID does not recover fully upon annealing and is attributed to degradation linked to the SiN:H–Si interface. This behavior is also exhibited by multi-crystalline silicon cells that have very low oxygen content and do not show any bulk degradation.